PARPi-FL - a Fluorescent PARP1 Inhibitor for Glioblastoma Imaging - Christopher P. Irwin; Yasiri Portorreal; Christian Brand; Yachao Zhang; Pooja Desai; Beatriz Salinas; Wolfgang A. Weber; Thomas Reiner (Neoplasia: An International Journal for Oncology Research, 2014)
New intravital optical imaging technologies have revolutionized our understanding of mammalian biology and continue to evolve rapidly. However, there are only a limited number of imaging probes available to date. In this study, we investigated in mouse models of glioblastoma whether a fluorescent small molecule inhibitor of the DNA repair enzyme PARP1, PARPi-FL, can be used as an imaging agent to detect glioblastomas in vivo. We demonstrated that PARPi-FL has appropriate biophysical properties, low toxicity at concentrations used for imaging, high stability in vivo, and accumulates selectively in glioblastomas due to high PARP1 expression. Importantly, subcutaneous and orthotopic glioblastoma xenografts were imaged with high contrast clearly defining tumor tissue from normal surrounding tissue. This research represents a step toward exploring and developing PARPi-FL as an optical intraoperative imaging agent for PARP1 in the clinic.